2006
DOI: 10.1063/1.2170581
|View full text |Cite
|
Sign up to set email alerts
|

Combined centroid-envelope dynamics of intense, magnetically focused charged beams surrounded by conducting walls

Abstract: In this paper we analyze the combined envelope-centroid dynamics of magnetically focused high-intensity charged beams surrounded by conducting walls. Similar to the case where conducting walls are absent, it is shown that the envelope and centroid dynamics decouple from each other. Mismatched envelopes still decay into equilibrium with simultaneous emittance growth, but the centroid keeps oscillating with no appreciable energy loss. Some estimates are performed to analytically obtain characteristics of halo fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…A more detailed analysis of the centroid nonlinear dynamics reveals that the onset of the instability is due to a bifurcation of the equilibrium solution r 0 = 0 caused by a collision with an unstable fixed point already present in the nonrelativistic case. 3,6,12 In Ref. 9 an analogous stability condition was derived for the trajectory of a single particle located at the centroid position.…”
Section: ͑5͒mentioning
confidence: 99%
See 4 more Smart Citations
“…A more detailed analysis of the centroid nonlinear dynamics reveals that the onset of the instability is due to a bifurcation of the equilibrium solution r 0 = 0 caused by a collision with an unstable fixed point already present in the nonrelativistic case. 3,6,12 In Ref. 9 an analogous stability condition was derived for the trajectory of a single particle located at the centroid position.…”
Section: ͑5͒mentioning
confidence: 99%
“…8 For the particular case of intense, continuous, and round beams propagating with nonrelativistic velocities throughout a conducting cylindrical pipe, it has been shown that despite the occurrence of an unstable orbit in the centroid dynamics of off-axis beams, 3 this orbit alone cannot be responsible for pushing rms matched beams toward the wall. 6 It was also found that there is virtually no coupling between the centroid oscillation and the beam particles dynamics, which prevents conversion of the centroid motion energy into beam particles thermalization and the overall degradation of the beam quality. 6 These results indicate that off-axis dynamics do not impose severe limitations in the transport of such beams.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations